A Waitlist Randomized Implementation Trial of Classroom Pivotal Response Teaching for Students With Autism. (March 2023) - Stahmer, Aubyn C.; Suhrheinrich, Jessica; Rieth, Sarah R.; Roesch, Scott; Vejnoska, Sarah; Chan, Janice; Nahmias, Allison; Wang, Tiffany
Classroom Pivotal Response Teaching (CPRT) is a community-partnered adaptation of a naturalistic developmental behavioral intervention identified as an evidence-based practice for autistic children. The current study evaluated student outcomes in a randomized, wait-list controlled implementation trial across classrooms. Participants included teachers ( n = 126) and students with autism ( n = 308). Teachers participated in 12 hours of didactic, interactive training and additional in-classroom coaching. Generalized Estimating Equations accounted for clustering. Adjusted models evaluated the relative effects of training group, CPRT fidelity, and classroom quality on student outcomes. Results indicate higher CPRT fidelity was associated with greater increases in student learning. Having received CPRT training predicted increased student engagement and greater decreases in reported approach/withdrawal problems. These differences may be linked to the theoretical foundations of CPRT of increasing student motivation and engagement and collaborative adaptation to increase feasibility in schools. Overall, results suggest CPRT may be a beneficial approach for supporting autistic students.